Pembelajaran Lintas Budaya Melalui Aktivitas Mengajar pada Sanggar Bimbingan Non Formal di Malaysia - Ardhana Januar Mahardhani; Sutrisno Sutrisno; Nurtina Irsad Rusdiani; Hadi Cahyono; Ambiro Puji Asmaroini; Dian Kristiana; Eka Destriyanto Pristi Ayuningtyas (Dharma Sevanam : Jurnal Pengabdian Masyarakat, 2023)
Cross-cultural introduction is something that must be done by a student and lecturer to Indonesian people who have lived in Malaysia for a long time. Cultural differences, even though they are still in the same Malay family, still have differences both in politeness in language, traditions that are carried out, and daily behavior. This activity is a form of implementing real work lecture activities carried out in Malaysia. The focus of its implementation is on non-formal guidance centers formed by groups of Indonesians residing in Malaysia. This guidance center carries out teaching and learning activities for the children of Indonesian migrant workers who have lived in Malaysia for a long time and the majority of them are non-documented workers. The implementation of this activity includes planning, implementing, and evaluating activities. The results that can be concluded in this activity are that cultural differences must be respected even though they come from one country but carry out all activities in different countries. Children who are active in the guidance center must be introduced to Indonesian culture even though they were born in Malaysia but are still Indonesian citizens.